Reading Trojan Rome: illegitimate epithets, avatars, and the limits of analogy in Silius Italicus' Punica - Cowan, R (2007)
Silius Italicus' Punica is about Roman identity, and one of his principal means of exploring that is through the complex negotiation of Rome's identity with Troy. This article examines two specific techniques which the epic employs: firstly, Silius' use of Trojan epithets for third-century Roman characters, which by its very inappropriateness foregrounds the complex play of similitude and dissimilitude between the peoples and their cities; secondly, the example of how L. Aemilius Paulus, the consul who died at Cannae, is subtly like and unlike his Trojan forebear Hector, a relationship problematized by further intertextuality with Aeneas, Turnus, Pompey, and others, but one which has significant implications for the relationship between Hector's Troy and Paulus' Rome.